A study in Bundelkhand region of Madhya Pradesh, India to assess the risk factors and correlates of pre-eclamptic toxemia - Pandey, Shikha; Pandey, Ramesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Pre-eclamptic toxemia is pregnancy-induced hypertension (PIH) manifesting in second trimester and affecting multiple systems. The objective was to study the factors of pre-eclampsia in pregnant women admitted for delivery in Bundelkhand Medical college hospital Sagar, Madhya Pradesh, India. Methods: A case-control study was conducted at Bundelkhand Medical College Hospital in Sagar, Madhya Pradesh, India. Criteria in selection of pregnant women with pre-eclampsia comprised those who had hypertension after the 20th week of gestation with associated proteinuria, and controls were pregnant women who were not diagnosed with pre-eclampsia. Total of 100 cases and 100 controls were selected for the year 2015. Factors in study included mother's age, parity, body mass index, history of chronic hypertension, history of diabetes, history of renal disease, family history of hypertension, and history of pre-eclampsia in earlier pregnancy. Crude and adjusted odds ratio with 95% CI and Chi-square test were used for statistical analysis. Results: Major risk factors identified in univariate analysis included before pregnancy body mass index (BMI >25) (OR=11.27), history of hypertension (OR=8.65), history of diabetes mellitus (OR=11.0), history of renal disorders (OR=7.98), familial history of hypertension (OR=5.4), history of PIH in earlier pregnancy (OR=9.63), and twin pregnancy (OR=4.85). As per multiple logistic regression analysis the pre-pregnancy BMI of >25 (OR=7.56), history of hypertension (OR=6.69), history of diabetes mellitus (OR=8.66), history of renal disease (OR=5.6), family history of hypertension (OR=5.48), and twin pregnancy (OR=5.73) are the significant risk factors of pre-eclampsia. Conclusions: The pregnant women at risk of pre-eclampsia should be identified early and high-quality antenatal care should be provided in order to minimize the complications of pre-eclampsia both for the mother and the fetus.